Catalytic Asymmetric Synthesis of N‐Chiral Amine Oxides. Issue 42 (6th October 2016) - Bhadra, Sukalyan; Yamamoto, Hisashi
Abstract: Direct asymmetric synthesis of N ‐chiral amine oxides was accomplished (up to 91:9 e.r.) by means of a bimetallic titanium catalyst. A hydroxy group situated at the γ‐position of the N stereocenter enables the desired N‐oxidation through dynamic kinetic resolution of the trivalent amine substrates. The method was further extended to the kinetic resolution of racemic γ‐amino alcohols with a preexisting stereocenter, giving an important class of enantioenriched (up to 99.9:0.1 e.r.) building blocks that are otherwise difficult to synthesize. Abstract : One‐sided : An asymmetric synthesis of N‐chiral amine oxides was developed that proceeds via dynamic kinetic resolution of unsymmetrical γ‐hydroxy tertiary amines. A binuclear titanium complex enables the desired hydroxy‐directed N‐oxidation process. The concept was further expanded to the kinetic resolution of racemic γ‐amino alcohols with a preexisting stereocenter.